Infection by the human papillomavirus in teenagers sexually active: clinic and subclinic manifestations - Derchain, Sophie; Neves-Jorge, Jessé de Paula; Andrade, Liliana; Pinto-Neto , Aarão Mendes; Silva, João Pinto e (São Paulo Medical Journal, 1995)
This research studies the association of the cervical condyloma with the intraepithelial neoplasia, during sex activity, pregnancy, diagnose methods, cytology and colposcopy in teenagers. The objective of this research is to study the propaedeutics for the uterine coli condyloma diagnose in a group of teenagers. For this purpose, we have studied 131 teenagers sexually active with ages between 14 and 19 years and presenting histologically confirmed uterine coli condyloma. Association with intraepithelial neoplasia, sexual ativity duration, method of diagnose, pregnancy analysis, cytology and colposcopy results and association with vulva and vagina injuries were evaluated. The high association rate with condyloma and intraepithelial neoplasia after a short time of sexual activity and the none presence of macroscopic warts in the genital organs in 80% of cases presenting cervical condyloma, demonstrate that: a more careful investigation with colposcopy.and biopsy of the inferior genitals of the women-teenagers sexually active is needed, when presenting modified cervical cytology.